The Influence of Religiosity and Destination Image on Tourist Loyalty Through Satisfaction: A Case of Halal Tourism in the Special Region of Yogyakarta - Hana Wira Pratiwi; Anas Hidayat (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2026)
This study aims to analyze the influence of religiosity and destination image on the Satisfaction and Loyalty of Muslim tourists at halal tourist destinations in the Special Region of Yogyakarta (DIY). The research population includes all tourists who have visited halal destinations in DIY, and sampling is conducted using convenience sampling, with a selected sample of 247 respondents. Data were collected via an online questionnaire and analysed using a mediation approach to test the direct and indirect effects among variables, which were subsequently tested using Smart PLS. The results showed that religiosity and destination image had a positive and significant effect on the Satisfaction and Loyalty of Muslim tourists. Tourists with high levels of religiosity felt more satisfied and were more loyal when their travel experiences aligned with Islamic values. Destination image that reflects hospitality, cleanliness, and the availability of halal facilities strengthens tourists' positive perceptions and trust. In addition, Satisfaction was found to mediate the relationship between religiosity and destination image on loyalty, indicating that spiritually meaningful experiences can foster emotional attachment and commitment to return.